Subject Coordinators : Leading Professional Development for Sessional Staff : Final Report. - Lefoe, Geraldine; Malfroy, Janne; McKenzie, Jo; Ryan, Yoni; Parrish, Dominique (Australian Learning and Teaching Council (ALTC), 2011)
Final report from the project 'Subject coordinators: Leading professional development for sessional staff".' It explored a leadership capacity development framework that includes targeted professional development as a means of improving academic leadership and management of sessional teaching teams. A leadership capacity development framework was developed that can be adapted for use in multiple institutions. The project also resulted in: Increased capacity of subject coordinators to manage their role as leaders and managers of sessional teaching teams through identification of relevant practices related to the Integrated Competing Values Framework; Improved communication and teamwork within the teaching teams involved through the focus on action learning projects; Development of resources to specifically promote good practices in regard to communication and teamwork within sessional teaching teams; Large scale practice sharing and some informal benchmarking of institutional practices and needs through the national workshop program and the website; and Raised awareness of strategies for influencing policy and procedural developments to acknowledge contributions of subject coordinators and sessional staff.